2023
DOI: 10.20473/jkl.v15i2.2023.92-98
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Tuberculosis in Toddlers and its Risk Factor at East Perak Health Center Surabaya

Alifa Salsabila Azzahrain,
Anisa Nur Afifah,
Laura Navika Yamani

Abstract: Introduction: Tuberculosis is a contagious disease that can grow fast due to its transmissibility through aerosols. One of the countries with the highest tuberculosis rates is Indonesia with a case fatality rate of 11.59%. This study's objective was to examine the relationship between the physical condition of the house and the immune system and the incidence of tuberculosis in toddlers in Surabaya. Methods: This study used an analytic survey research design with a case control research methodology. The case p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…While there is some evidence indicating a relationship between humidity and tuberculosis transmission, further research is still needed to fully understand the interaction between humidity and this disease. 20,22,[55][56][57] In this research, no correlation was found between rainfall and tuberculosis. However, during the period of 2013-2020, the presence of tuberculosis in Kolaka Regency tended to increase.…”
Section: Discussioncontrasting
confidence: 52%
“…While there is some evidence indicating a relationship between humidity and tuberculosis transmission, further research is still needed to fully understand the interaction between humidity and this disease. 20,22,[55][56][57] In this research, no correlation was found between rainfall and tuberculosis. However, during the period of 2013-2020, the presence of tuberculosis in Kolaka Regency tended to increase.…”
Section: Discussioncontrasting
confidence: 52%
“…Tabel 2 menunjukan hasil diagnosis oleh tim ahli klinis dari IDI dan IDAI. (Aziz, 2018;Azzahrain, Alifa Salsabila & Yamani, 2023;Budiati & Khoirina, 2018;Rahmawati & Rosita, 2021).…”
Section: Gambar 2 Dokumentasi Pelaksanaan Kegiatanunclassified